Climate changes and their impact on the extinction of living organisms in an environment Marsh Chibayish. - فاضل عبد آل وشاح قصي (Journal of College of Education, 2021)
The study aims to reveal the extent of the impact of climate change on the biological diversity in the environment of the Chibayish Marshlands and to know the extent of the risk of this on plant and animal organisms. Therefore, the study came with two studies. The first discussed climate changes in the marshes, focusing on the temperature and the amount of rain falling. The first two periods were in the seventies. (1970-1979) of the last century, if the marshes were of their nature, full area, and relatively fresh water, and the comparison was made with the first decade of the current century (2001-2010) in which the climatic changes were evident, which affected the ecosystem in the marshes, especially the drought that afflicted the region and the high concentration of salt In what remains of the water bodies in the marshes, and thus its reflection on the threat to the life of the neighborhoods and biological diversity in the region, as stated in the second topic of the study.